Gambaran Kualitas Hidup Pasien Osteoartritis Lutut di Poliklinik Khusus Penyakit dalam RSUP Dr M Djamil Padang - Shamimi Mazli; Noverial Noverial; Miftah Miftah; Yevri Yevri; Rose Dinda; Shinta Shinta (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
The high prevalence of knee osteoarthritis is influenced by increasing life expectancy and increasing elderly population. Knee osteoarthritis is a degenerative disease that causes disability in sufferers, thus having a negative impact on the patient's quality of life. This can be measured using the Short Form (SF) 36 instrument, which is a standard quality of life measuring tool and is often used by many researchers. This research generally aims to determine the quality-of-life scores of patients and the characteristics of knee osteoarthritis sufferers at Dr.M. Djamil General Hospital, Padang. This research is a descriptive study with a cross-sectional research design. Data collection was carried out by distributing the SF-36 questionnaire to outpatient knee osteoarthritis patients at Dr.M.Djamil Padang Hospital and the respondent data obtained was primary data from 74 patients taken according to the inclusion criteria. The results of the SF-36 questionnaire showed that from seven aspects, namely physical aspects, physical limitations, body pain, general health, vitality, social function and emotional limitations, the quality of life was found to be poor except for the mental health dimension. The distribution of gender characteristics is that women are more numerous than men, the highest age group is the early senior age group (46-55 years), not working patients, patients with a high school education level, and has comorbidities. The most common location of osteoarthritis occurs in both knees (bilateral), suffering from the disease for more than 6 months, with a BMI of 25 – 29.9 (obesity I) and most patients received pharmacological therapy. The majority of outpatients with knee osteoarthritis have poor quality of life.